# how to write for loop for this case?

1 view (last 30 days)
bahareh bshrt on 10 Feb 2021
Answered: Manash Sahoo on 10 Feb 2021
I have this relation
deltaT=50;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T0+(deltaT*F_e);
T50=K_eff\F_eff;
deltaT=100;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T50+(deltaT*F_e);
T100=K_eff\F_eff;
deltaT=150;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T100+(deltaT*F_e);
T150=K_eff\F_eff;
can anyone help me to write code for this?(code for deltaT & Tn)

Manash Sahoo on 10 Feb 2021
Could you elaborate on your question? Are you trying to execute this code in the context of a for loop? Additionally, I don't see a variable named "Tn".
But, if your question is how to turn this code into a for loop with 'deltaT' as the iterating variable, try this:
for deltaT = 0:50:150
if deltaT == 0
deltaT = 1;
end
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T0+(deltaT*F_e);
T50=K_eff\F_eff;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T50+(deltaT*F_e);
T100=K_eff\F_eff;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T100+(deltaT*F_e);
T150=K_eff\F_eff;
end